A systematic literature review on current status and future prospects of pre-harvest sprouting management in rice - Deepika, J; Vijayalakshmi, D; Aravind Kumar, S; Vinitha, A; Ravichandran, V; Vellaikumar, S; Thirukumaran, K (Plant Science Today, 2024)
Pre-harvest sprouting (PHS) is a major constraint to rice in areas having high rainfall during late maturity. It poses a significant challenge to farmers, leading to yield loss and grain quality. Prolonged wet and humid conditions prevailing in North East India and incidence of cyclonic storms and heavy floods in other states cause PHS in rice. This systematic literature review (SLR) explored existing research on PHS's physiological, biochemical, molecular and environmental factors. A thorough approach that included a methodical Scopus literature search turned up 1236 papers, of which 60 research were selected for quantitative analysis following inclusion criteria. The papers dissected the genetic basis, population studies and genome analysis. Findings of seed dormancy regulation, Quantitative trait loci (QTLs) associated with PHS resistance, genes involved in improving seed dormancy, reducing abscisic acid sensitivity and breeding RILs and NILs resistant to PHS were published. Molecular and biochemical studies reported heat shock proteins (HSPs), hormone-related genes (ABA and GA) and microRNAs as potential targets for developing strategies to prevent PHS in rice. Resilience to pre-harvest sprouting was attempted through exogenous application of chemicals such as eugenol, sodium chloride, glucose, coumarin, molybdenum, maleic hydrazide and uniconazole. Despite current management practices, challenges persist due to the absence of universally resistant varieties and the variability in environmental conditions. Potential gaps identified were a lack of research papers from Indian authors on PHS, a simple and novel technology for the farming community to arrest PHS under unfavourable environmental conditions. Future research directions emphasize integrating laboratory insights into genetic and molecular mechanisms into practical field technologies.